The Effects of Habitus on Contemporary Global Ceramics Sample (Sean Erwin) - Muhammad, Hanin Wissam; Karim, Rana Dahi Abdul (Journal of Posthumanism, 2025)
Habitus is one of the pivotal terms that entered the field of visual arts in the direction of postmodernism through the ideas and methods of each artist in general and the potter in particular, which greatly affected society and through its connection to contemporary arts and not being subject to fixed traditional concepts or rigid aesthetic frameworks and trying to reveal the nature of its influence in societies as a social phenomenon that affects the artwork and at other times as a concept in the artwork itself and according to what contemporary artistic trends produced in terms of a transformation in ideas, concepts and phenomena that affected the product of the ceramic achievement as a work produced according to renewed standards not subject to standards through connotations and functions and what goes with the tendencies of the time and the spirit of the age and in light of this renewed multiplicity through the comprehensive change that occurred in the nature of contemporary society and what the artist moves forward with in complying with the logic of his interest and keeping pace with it. Thus, habitus becomes like the psychological climate from which the potter produces his own styles, expressions and feelings, which clarifies to what extent contemporary arts are moving towards. Its transformations and breadth of representation represent an extension of the state of society and its profound transformations without losing its connection to its cultural and social roots, which are its record and reference.